The encoded codex: a digital, statistical, and codicological examination of Paris, Bibliothèque nationale de France, fonds français, 24432 - Dows-Miller, SH (2024)
The main objective of this thesis is methodological, showing the value of using methods from the digital humanities alongside analogue approaches to expand our understanding of Western medieval manuscripts and their texts. I take as a case study a manuscript collection of Old and Middle French texts (Paris, Bibliothèque nationale de France, fonds français, 24432), which has been puzzlingly neglected by scholarship.